Pseudomonas aeruginosa Strain-sharing in Early Infection Among Children With Cystic Fibrosis. (16th June 2020) - Stapleton, Patrick J; Izydorcyzk, Conrad; Clark, Shawn; Blanchard, Ana; Wang, Pauline W; Yau, Yvonne; Waters, Valerie; Guttman, David S
Abstract: Background: We previously identified Pseudomonas aeruginosa isolates with characteristics typical of chronic infection in some early infections in children with cystic fibrosis (CF), suggesting that these isolates may have been acquired from other patients. Our objective was to define the extent of P. aeruginosa strain-sharing in early CF infections and its impact on antibiotic eradication treatment failure rates. Methods: We performed whole genome sequencing on isolates from early pediatric CF pulmonary infections and from the following comparator groups in the same hospital: chronic CF infection, sink drains, sterile site infections, and asymptomatic carriage. Univariate logistic regression was used to assess factors associated with treatment failure. Results: In this retrospective, observational study, 1029 isolates were sequenced. The CF clones strain B and clone C were present. In 70 CF patients with early infections, 14 shared strains infected 29 (41%) patients over 5 years; 16% (n = 14) of infections had mixed strains. In the 70 children, approximately one-third of shared-strain infections were likely due to patient-to-patient transmission. Mixed-strain infections were associated with strain-sharing (odds ratio, 8.50; 95% confidence interval, 2.2–33.4; P = .002). Strain-sharing was not associated with antibiotic eradication treatment failure; however, nosocomial strain transmission was associated with establishment of chronic infection in a CF sibling pair. Conclusions: Although early P. aeruginosa CF infection is thought to reflect acquisition of diverse strains from community reservoirs, we identified frequent early CF strain-sharing that was associated with the presence of mixed strains and instances of possible patient-to-patient transmission. Abstract : In this study, 41% of children with cystic fibrosis shared Pseudomonas aeruginosa strains with other children. In approximately one-third of patients with shared strains, epidemiologic links were identified, suggesting that patient-to-patient transmission of P. aeruginosa strains may have occurred.